Legal Analysis Of The Implementation Of The Minister Of Religious Affairs Regulation Number 12 Of 2019 Concerning The Ethics And Behavior Of State Civil Apparatus Employees In The Ministry Of Religious Affairs Environment Towards Employee Performance At The Ministry Of Religious Affairs Office In Serang City - Aqil Meilanggi Shihab; M. Nassir Agustiawan; Mohammad Hifni (Yayasan pendidikan dzurriyatul Quran, 2025)
The State Civil Apparatus (ASN) plays a central role in government administration and maintaining national integrity based on the values of Pancasila and the 1945 Constitution. Professionalism and work ethics are essential for creating a bureaucracy free from corruption, collusion, and nepotism. This study aims to analyze the role of civil servants within the Ministry of Religious Affairs of Serang City based on Ministerial Regulation Number 12 of 2019 and to assess the effectiveness of its implementation on employee performance. The research employs a normative legal method with a statutory approach, utilizing primary data from interviews and secondary data from primary, secondary, and tertiary legal materials. The results indicate that civil servants hold a vital role as public servants, yet the enforcement of sanctions for ethical violations remains weak, resulting in a lack of deterrence. Strengthening disciplinary enforcement is therefore necessary to uphold the professionalism and integrity of civil servants in public service